Cystic Esophageal Gastrointestinal Stromal Tumor (GIST): A Rare presentation - Junaid Iqbal; Sadia Rashid; Hina Pathan; Sorath Murtaza (Journal of Bahria University Medical and Dental College)
Gastrointestinal stromal tumors (GIST) are solid tumors of the gastrointestinal tract. The stomach is the most common site while the esophagus is the least common site for gastrointestinal stromal tumors. The cystic Gastrointestinal stromal tumor has never been reported in the past. On CT scan of a young male patient, we reported an exophytic cystic structure of 2.5 x 2.2 cm along the esophagus as an esophageal duplication cyst then he underwent an image-guided biopsy that finally turned out to be a Gastrointestinal stromal tumor on histopathology. He underwent surgical resection; he is now symptomsfree and on 6 monthly CT scan follow-ups